A model to characterize the effect of cross phase modulation on polarization in an optical fiber transmission system - Thiam, Sim Ngee; Rahman, Faidz Abd. (ELSEVIER GMBH, 2007)
This paper presents a model that described the process of inter-influence between cross phase modulation (XPM) and polarization effects such as polarization mode dispersion (PMD) and polarization dependant loss (PDL) in an optical fiber communication system. Previous papers have discussed PMD-PDL and PMD-XPM effects in separate models, but in this work we developed a model that is capable of characterizing and evaluating PMD, PDL and XPM simultaneously. From the model, we found that PMD and PDL can be affected by XPM. The presence of XPM changed the vector directions of PMD and PDL in Stokes space. (c) 2006 Elsevier GmbH. All rights reserved.